2019
DOI: 10.1039/c9ob00166b
|View full text |Cite
|
Sign up to set email alerts
|

Selective synthesis of spirooxindoles via a two-step reaction of N-phenacylpyridinium bromide, 1,3-indanedione and N-alkylisations

Abstract: The three-component reaction resulted in the unique spiro[indoline-3,4′-naphtho[1,2-b]furan] derivatives, which were converted to spiro[indoline-3,2′-naphthalen]-4′-yl acetates by acylation and alkoxy-substituted spiro[benzo[h]chromene-5,3′-indolines] by acid catalyzed etherification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

6
4

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…Therefore, combination of the generation of azomethine ylides with direct β-C–H functionalization of the cyclic amines would result in a conjugated azomethine ylide, which opened up new potential applications of 1,3-dipolar cycloaddition and developed the molecular diversity of N-heterocycles . In order to investigate the synthetic values of the conjugated azomethine ylides in the 1,3-dipolar cycloaddition reaction and in continuation our aim of developing efficient synthetic methods for diverse spirooxindolines, , herein we wish to report the three-component reaction of pyrrolidine, aromatic aldehydes, and various cyclic dipolarophiles such as 3-arylideneoxindoline-2-ones, 2-arylidene-1,3-indanediones, and 3-phenacylideneoxindolies for synthesis of novel functionalized spiropyrrolidine derivatives. Additionally, some of the synthesized spirooxindoles have been preliminarily demonstrated by in vitro evaluation against mouse colon cancer cells CT26 and human liver cancer cells HepG2 by MTT assay.…”
Section: Introductionmentioning
confidence: 91%
“…Therefore, combination of the generation of azomethine ylides with direct β-C–H functionalization of the cyclic amines would result in a conjugated azomethine ylide, which opened up new potential applications of 1,3-dipolar cycloaddition and developed the molecular diversity of N-heterocycles . In order to investigate the synthetic values of the conjugated azomethine ylides in the 1,3-dipolar cycloaddition reaction and in continuation our aim of developing efficient synthetic methods for diverse spirooxindolines, , herein we wish to report the three-component reaction of pyrrolidine, aromatic aldehydes, and various cyclic dipolarophiles such as 3-arylideneoxindoline-2-ones, 2-arylidene-1,3-indanediones, and 3-phenacylideneoxindolies for synthesis of novel functionalized spiropyrrolidine derivatives. Additionally, some of the synthesized spirooxindoles have been preliminarily demonstrated by in vitro evaluation against mouse colon cancer cells CT26 and human liver cancer cells HepG2 by MTT assay.…”
Section: Introductionmentioning
confidence: 91%
“…Oxa-Michaelealdol condensation reactions of salicylaldehydes with sugar-derived 3-C-vinyl sugar nitro olefins carried out in the presence of triethylamine under neat conditions afford (2S)-2-C-spiroglycosyl-3-nitrochromenes, in moderate to good yields (19OBC74). Two-step syntheses of spiroindolinone benzo[h]chromene derivatives are accomplished via three-component reactions of N-alkylisatins with indane-1,3-dione and two equivalents of N-phenacylpyridinium salts in the presence of triethylamine in refluxing acetonitrile, subsequent purification followed by treatment of the obtained residue dissolved in alcohol with p-TsOH (Scheme 23) (19OBC3978).…”
Section: Scheme 21mentioning
confidence: 99%
“…2 in Scheme 1). For further exploiting the synthetic values of this domino annulation reaction for synthesis of the diverse polycyclic spirooxindoles and related compounds, [12] two kinds of o-hydroxylsubstituted chalcones were introduced in the reaction, we successfully found that the hydroxyl group not only alternated the direction of ring expansion, but also took part in the formation of the different polycyclic spirooxindoles (Eq. 3 in Scheme 1).…”
Section: Introductionmentioning
confidence: 99%